2015
DOI: 10.1016/j.joca.2014.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Utility of T2 mapping and dGEMRIC for evaluation of cartilage repair after allograft chondrocyte implantation in a rabbit model

Abstract: T2 mapping and dGEMRIC were both effective for evaluating tissue repair after allograft chondrocyte implantation. ΔR1 values of dGEMRIC represented good correlation with histologically and biochemically even at early stages after the implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
0
11
0
2
Order By: Relevance
“…Assim, a RM destacou-se como uma importante ferramenta diagnóstica, uma vez que permitiu a detecção de alterações no processo de reparação dos enxertos osteocondrais. A RM é reconhecida como um método não invasivo para examinar patologias articulares e uma referência efetiva para avaliar a reparação em cartilagens (Goebel et al 2012, Rodríguez--Merchán 2012, Bekkers et al 2013, Endo et al 2015, Obara et al 2015. Além disso, a RM também pode ser útil na identificação de lesões ósseas ocultas à radiografia convencional, incluindo as contusões ósseas e fraturas osteocondrais, que representam sítios de hiperemia, edema ou hemorragia óssea (Grossi et al 2001, Kido et al 2014.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Assim, a RM destacou-se como uma importante ferramenta diagnóstica, uma vez que permitiu a detecção de alterações no processo de reparação dos enxertos osteocondrais. A RM é reconhecida como um método não invasivo para examinar patologias articulares e uma referência efetiva para avaliar a reparação em cartilagens (Goebel et al 2012, Rodríguez--Merchán 2012, Bekkers et al 2013, Endo et al 2015, Obara et al 2015. Além disso, a RM também pode ser útil na identificação de lesões ósseas ocultas à radiografia convencional, incluindo as contusões ósseas e fraturas osteocondrais, que representam sítios de hiperemia, edema ou hemorragia óssea (Grossi et al 2001, Kido et al 2014.…”
Section: Discussionunclassified
“…Constitui-se um exame não radio-ionizante e não invasivo de escolha para se avaliar a lesão e os processos de reparação articulares. Permite a visualização detalhada dos tecidos intra-articulares, fornecendo contraste diferenciado entre os tecidos moles em diferentes ponderações de imagem e com capacidade multiplanar (Muglia et al 2001, Efe et al 2012, Blackman et al 2013, Endo et al 2015. A partir da utilização de técnicas específicas para a região articular, a RM fornece informações sobre as alterações de sinal do tecido cartilaginoso, da morfologia da superfície articular e do osso subcondral (Rodrigues & Camanho 2010, Kido et al 2014.…”
Section: Introductionunclassified
“…Articular cartilage defect caused by trauma or degenerative pathology is major challenge because of the poor intrinsic healing potential of cartilage. Many attempts including bone marrow stimulation technique, allograft or autograft transplantation, tissue engineering, and autologous chondrocyte implantation procedures have been conducted to repair cartilage defects 27 28 29 . However, no techniques in the literature have been reported to be able to regenerate functional cartilage similar to the quality of native cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MRI could be useful both during bioreactor cultivation and upon surgical implantation in a noninvasive manner . A recent study demonstrated the effectiveness of quantitative MRI for evaluating the quality of cartilage repair by a 3D scaffold implanted in osteochondral lesions, following allograft chondrocyte implantation over time . It has been used for biomechanical measurements in cartilage and related joint tissues and, in comparison with other modalities, MRI provides an extensive range of functional measures at the tissue level .…”
Section: Available Imaging Techniquesmentioning
confidence: 99%